A produção da (in)disciplina escolar: normalização, subjetivação e controle - Almeida, Nathália Suppino Ribeiro de (2021)
This study deals with the issue of school discipline and indiscipline from the teachers' narratives collected from effective teachers in public elementary schools in the city of Ribeirão Preto–SP. Therefore, we aim to investigate the normalizing process as a condition to produce school (in)discipline based on reports of experiences lived by teachers in their daily lives on issues involving the subject under analysis. The central perspective of the analysis is that discipline and indiscipline are the result of a production that takes place in the school institution, being inseparable from the elements, phenomena and relationships that produce them and that reverberate their effects on the way in which the subjectivities of those involved are constituted. in the schooling of children. These elements, phenomena and relationships were observed from the teachers' narratives collected in conjunction with the theoretical assumptions studied regarding the normalization process and disciplinary power. Among the various aspects discussed, we consider that not only students, but teachers, can produce and be produced under permanent surveillance, examination, standardization, control or correction directed at them according to the regime of truths established in their experiences. And, if on the one hand the narratives indicate that disciplinary practices are part of school demands, we emphasize that they are elements of a conflicting process in which, despite being constantly affirmed, the disciplinary power can also be denied, frustrated and threatened . The selected methodological bases are based on qualitative approaches, semi-structured recorded biographical interviews, bibliographic study and biographical research. The analysis of the collected data was carried out in the light of the biography of the experiences reported, that is, of a methodological approach that encompasses reflections on the subjects' acts and thoughts in a complex of relationships that permeate their experiences and the elements that make up their surroundings, inscribing them in the representations he makes about himself, the other and the group he belongs to. After the analyses, we found a disciplinary production based on the subject's normalization process consolidated and, in the direction of reflections on the production of discipline and school indiscipline and its effects, we believe that we think about them from the perspective of problematizing and denaturalizing this process, through the courage to tell the truth, could place them in a field of possibilities for criticism and reinvention.